STRUGGLE AGAINST HEGEMONY IN THE ADVENTURES OF HUCKLEBERRY FINN AND THE KITE RUNNER - Alfi Muhammad Firdaus; Mahi M. Hkikmat (CALL, 2021)
Novels The Adventures of Huckleberry Finn written by Mark Twain and The Kite Runner written by Khaled Hosseini have similarities in describing struggle against hegemony. The term of “hegemony” is related to a domination of dominant group to subordinate group through agreement. In addition, this hegemony can also include physical violence to strengthen the domination. Meanwhile the term “Struggle” means that there are also resistances against the hegemony. These two novels were analyzed by comparative literature theory by Susan Basnett and Antoni Gramsci’s theory about hegemony. Focus of this research is how the writers describe hegemony and counter hegemony in social environment through literary work. This research aims to describe hegemony from dominant group to subordinate group in several kinds such as culture, ideology, intellectual and moral leadership, and state. This research also describes about several resistances, such as active, passive, and humanistic resistance. The result of this research is that there are similarities and differences of hegemony and counter hegemony based on state of factor of American and Afghanistan. The similarities can be found in the struggle, such as passive and humanistic resistance. Meanwhile for the difference in hegemony, the novel The Kite Runner includes physical hegemony through war and assassination. For the difference in struggle, The Kite Runner provide an active resistance toward a dominant group.Keywords: Hegemony; Counter Hegemony; Comparative Literature